L-PS-M hierarchical evolution target system framework for telecommunications service support system - QIAO Wen; WANG Peng; WANG Shoufeng; YANG Aidong; OUYANG Ye (Dianxin kexue)
With the continuous development of communication technology and the accelerated arrival of enterprise digitization, the telecom business support system is also evolving and changing. In order to realize the goal of high-quality, high-efficiency and sustainable evolution, telecom operators need to establish an effective and adaptive to the market demand of business support system hierarchical evolution target system. Based on the analysis of the basic characteristics of the current telecom business support system and the demand of operation services, a framework of L-PS-M (level-process-system-measurement) hierarchical evolution target system for telecom operation service support was proposed. The framework firstly constructed a three-dimensional cube mapping structure formed by the three dimensional factors of end-to-end business process, system support capability, and hierarchical goal. Secondly, a subdivided implementation path of the operation service support system was given. Thirdly, telecom carriers could carry out the planning and optimization of the system support capability according to the actual demand in a targeted way through the implementation path, so as to improve the efficiency of the operation and system production, and further clarified the evolution of the business support system, which was applicable to telecom operations. It further clarified the evolution direction of the business support system.